INFLUENCING FACTORS IN MMR IMMUNISATION DECISION MAKING - Marie C. Hill; Carol L. Cox (European Scientific Journal, ESJ, 2013)
Immunisation of children is not a straightforward process for parents. The United Kingdom [UK] has a structured immunisation programme which continues to evolve and develop in meeting the demand to improve and control preventable infectious diseases. Following a measles outbreak in Quebec, Canada in 1989 it was suggested that a single Measles, Mumps and Rubella [MMR] vaccine did not provide enough seroprotection to ensure herd immunity levels of 95%. Therefore the UK introduced a second dose of the vaccine in 1996. Factors influencing parental decision making in relation to uptake of the MMR vaccine are the prevention of disease, the consequences of contracting infectious diseases, perceived pain and the media. Practice Nurses are a credible source of information that parents actively seek to inform their decision making in relation to the immunisation of their children. Immunisation decision making is not a straightforward process for parents. Many factors influence parental decision making on whether they immunise their child with the Measles, Mumps and Rubella [MMR] vaccine. The feasibility study described in this article provides insight into influencing factors associated with decisions regarding the immunisation of children by parents. The study findings suggest the practice nurse is a credible source of information parents actively seek to inform decision making. At a time when the incidence of measles and mumps is rising in the United Kingdom [UK] the provision of appropriate information by the Practice Nurse has the potential to increase uptake of the MMR vaccine.